Tradisi Nasi Berkat dan Kesuburan Lahan Garapan dalam Praktik Tawasul: Studi Living Qur’an Di Sumatera Utara - Husna, Nurul; Sari, Maula (ojs.unsiq.ac.id, 2023)
Religious rituals no longer only contain religious values, but have also expanded to contain the economic system. Religious rituals are a cultural asset owned by the community. Thus, the attraction of the implementation of the ritual is not only in demand or followed as a place of religious tourism, but can advance the source of community economic prosperity through the fertility of arable land. The type of research in this article is field research using sociological and anthropological approaches. This study uses Anthropological (Cultural and Religious) theory. The results of this study are that the practice of tawassul on blessed rice is carried out in Besilam for the fertility of arable land in terms of the Socio-Religious aspect of talking about social phenomena, and viewing religion as a social phenomenon that has a relationship between religion and society. That is how far religion and religious values play a role in society. With this activity, the people of Besuilam believe that God helps and blesses their agricultural land by making it fertile and prospering the community. Keywords: Tradition, Living Qur'an, Social Religion